Regiocontrolled SNAr Reaction on 2,3-Dihalopyridines with NaSMe To Obtain Bromo(methylthio)pyridines as Key Precursors of 3-Halo-2-(hetero)arylthieno[2,3-b]pyridines and Thieno[3,2-b]pyridines - Begouin, Agathe; Peixoto, Daniela; Queiroz, Maria-João R. P. (Synthesis, 2013)
The synthesis of 3-halo-2-(hetero)arylthieno[2,3-b]pyridines and 3-halo-2-(hetero)arylthieno[3,2-b]pyridines has been performed through a three-step methodology from 3-bromo-2-chloropyridine or 2-bromo-3-fluoropyridine, respectively. The key step of this methodology is the formation of the required bromo(methylthio)pyridines by a regiocontrolled nucleophilic aromatic substitution (SNAr) with sodium methanethiolate (NaSMe). Then, the Sonogashira coupling with (hetero)arylalkynes followed by a halocyclization with bromine or iodine, afforded the expected 3-halo-2-(hetero)arylthienopyridines.
Keywords: thienopyridines; nucleophilic aromatic substitution; methanethiolate; Sonogashira coupling; halocyclization